PERBEDAAN KADAR KOLESTEROL LDL DARAH TIKUS SPRAGUE DAWLEY PADA PEMBERIAN KOPI FILTER DAN TANPA FILTER - Sari, Raysa Tanjung; Puruhita, Niken (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background : Coffee contains cafestol and kahweol which can increase LDL cholesterol levels. Effect of cafestol and kahweol with chlorogenic acids are antagonist in coffee. Chlorogenic acids is strong antioxidant in coffee. Unfiltered coffee contains more chlorogenic acids and cafestol than filtered coffee. The study aims to determine the differences of LDL cholesterol levels of Sprague Dawley rats in giving filtered and unfiltered coffee. Methods : a laboratory experimental study, with randomized pre-post test control group design, with a simple random sampling to 28 Sprague Dawley rats were divided into 3 groups. The first treatment was given unfiltered coffee 4x2.7 ml, the second treatment was given filtered coffee 4x2.7 ml and the control was given water 4x2.7 ml for 28 days. LDL cholesterol levels were determined by the homogenous enzyme method. Data were analyzed by paired t-test and Oneway ANOVA test at 95% confident level. Results : Changes levels of LDL cholesterol in filtered coffee (0.85 mg/dl) are higher than unfiltered coffee (0.15 mg/dl). However statistical test shows there is no significant difference of LDL cholesterol in filtered and unfiltered coffee (p>0.05). Conclusion : There is no significant difference of LDL cholesterol levels of Sprague Dawley rats in filtered and unfiltered coffee.